2006
DOI: 10.1002/aris.1440400112
|View full text |Cite
|
Sign up to set email alerts
|

Semantic relations in information science

Abstract: Abstract. This chapter examines the nature of semantic relations and their main applications in information science. The nature and types of semantic relations are discussed from the perspectives of linguistics and psychology. An overview of the semantic relations used in knowledge structures such as thesauri and ontologies are provided, as well as the main techniques used in the automatic extraction of semantic relations from text. The chapter then reviews the use of semantic relations in information extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 238 publications
(302 reference statements)
0
86
0
6
Order By: Relevance
“…it is influenced by culture and educational background. As stated previously, prior research has shown a significant cross-cultural overlap [29], [30], [31], [32], [33], [34] on the relatedness ratings of certain kinds of semantic knowledge. Relations between most natural, physical and biological concepts, e.g.…”
Section: Measurement Processesmentioning
confidence: 91%
See 1 more Smart Citation
“…it is influenced by culture and educational background. As stated previously, prior research has shown a significant cross-cultural overlap [29], [30], [31], [32], [33], [34] on the relatedness ratings of certain kinds of semantic knowledge. Relations between most natural, physical and biological concepts, e.g.…”
Section: Measurement Processesmentioning
confidence: 91%
“…One of the main advantages in using human processing is that much of the knowledge stored in semantic memory has a high inter-human correlation, i.e. a large fraction of this knowledge is consistent among most people [29], [30], [31], [32], [33], [34].…”
Section: Pre-considerations and High-level Descriptionmentioning
confidence: 99%
“…However, this is not the only issue. In their review of semantic relations in information science Khoo et al (2006) concluded that "no systematic analysis of the type of semantic relations used in ontologies has been reported in the literature." One implication of this conclusion is that there is no easy way of verifying whether the type of ontology or knowledge base that would contain the relations that are of interest to researchers in specialized domains already exists.…”
Section: Related Workmentioning
confidence: 99%
“…Although precoordinated indexing (an example is the Library of Congress Subject Headings) has supported associations between index terms as far back as 1967, Farradane pointed out that such implied relations expressed through precoordinated indexing are unambiguous only in a narrow domain (Khoo et al, 2006). Automated relation extraction is an active area of research (Moldovan, 2000;Khoo et al, 2006;Frunza et al, 2011;Arighi et al, 2013, Konstantinova, 2014 and approaches tend to cluster around two different strategies. At one end of the spectrum are the domain specific relations that operate over particular entities, as is typified in biomedicine where gene-protein or protein-locations (Kim et al, 2003) have been well explored.…”
Section: Introductionmentioning
confidence: 99%
“…Recognition [4], Semantic Role Identification [5], and Relation Extraction [6], [7]. Considering technology as applied science, then scientific publications can be considered as a primary source of information about technologies and emerging technological trends.…”
Section: Introductionmentioning
confidence: 99%